Comparison of the disinfectant effects of Nanosil D2 and Korsolex extra solutions on thermoset acrylic resin contaminated with Streptococcus mutans and Bacillus subtilis - Tahereh Ghaffari; Fahimeh Hamedi Rad; Tahereh Pirzadeh; Gahanbaksh Asgari (Wolters Kluwer Medknow Publications, 2019)
This study was conducted to compare the disinfectant effects of Nanosil D2 and Korsolex extra on thermoset acrylic resin contaminated with Streptococcus mutans and Bacillus subtilis. In this experimental study, 90 acrylic samples were made and sterilized. Two samples were cultured as a sterilization control in brain-heart infusion (BHI) and the rest of samples were divided into two groups. Samples of one group were placed in a bacterial suspension of S. mutans and the samples of another group were placed in a suspension containing B. subtilis. Each group was divided into two subgroups for immersion in Nanosil or Korsolex extra solutions. Seven samples were selected from each group at each of 30 min, 1 h, and 2 h and transferred to the BHI test tube, and their turbidity was evaluated after 24 h. SPSS 17 software was used to analyze the data, and the significance level of test was considered P < 0.05. At 1 h, Bacillus level of Nanosil D2 was significantly lower than that of Korsolex extra, and at all ½, 1, and 2 h, the level of Streptococcus in Nanosil D2 solution was significantly lower than that of Korsolex extra (P < 0.05). Bacillus and Streptococcus levels showed significant reduction in both solutions over time. The disinfecting power of Nanosil D2 is more than that of Korsolex extra.